Synthesis and Antibacterial Activities of Novel N-(5-Chloro-o-hydroxyphenyl) Amino Acid Copper Complexes - Liu, Jin-Biao; Xin, Chun-Wei; Liu, Fang; Lu, Jun-Rui; Wei, Rong-Bao (Asian Journal of Chemistry, 2011)
A number of N-(5-chloro-o-hydroxyphenyl) substituted amino acids and their copper complexes have been synthesized and tested for their antibacterial activities. The chemical structures of newly synthesized copper complexes were justified on the basis of spectral and elemental methods of analyses. Investigation of antibacterial actibity of the compoundes was done by serial dilution method using gram-positive, gram-negative bacteria and fungi. Among the compounds tested C1-C5 exhibited good antibacterial activities against Monilia albicans and Escherichia coli than L1-L5, but showed mild against Staphylococcus aureus.